2023
DOI: 10.3390/app132111723
|View full text |Cite
|
Sign up to set email alerts
|

Crash Severity Analysis of Young Adult Motorcyclists: A Comparison of Urban and Rural Local Roadways

Thanapong Champahom,
Chamroeun Se,
Fareeda Aryuyo
et al.

Abstract: In developing nations, motorcycles are a ubiquitous mode of transportation on local road networks, contributing to a substantial frequency of traffic accidents and fatalities. These occurrences exhibit significant discrepancies between urban and rural road environments. Specifically, urban roads exhibit greater traffic density and more robust law enforcement presence compared to their rural counterparts, factors that invariably influence vehicular speeds. Consequently, these variations in speed are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Notably, accidents resulting in fatalities are frequently observed on major arterial roads and highways [8]. A recent study conducted by Champahom et al [9] involved a comprehensive analysis of crash severity and revealed notable disparities in risk behaviors among motorcycle riders in urban and rural areas. Furthermore, studies from the United States suggest that motorcycle riders face a higher likelihood of fatal accidents in urban areas compared to rural areas [10].…”
Section: Urban and Rural Areasmentioning
confidence: 99%
“…Notably, accidents resulting in fatalities are frequently observed on major arterial roads and highways [8]. A recent study conducted by Champahom et al [9] involved a comprehensive analysis of crash severity and revealed notable disparities in risk behaviors among motorcycle riders in urban and rural areas. Furthermore, studies from the United States suggest that motorcycle riders face a higher likelihood of fatal accidents in urban areas compared to rural areas [10].…”
Section: Urban and Rural Areasmentioning
confidence: 99%
“…Currently, the policy of European Union countries and many countries around the world is aimed at reducing the number of fatalities in road accidents. The "Vision Zero" philosophy adopted by most of these countries around the world aims to create and monitor a road transport system in which human error will not result in death or serious injury [1][2][3]. Failure to adjust speed to prevailing road conditions and failure to maintain a safe distance from the vehicle in front are the most common driver errors leading to road accidents.…”
Section: Introductionmentioning
confidence: 99%